Prevalence of Salmonella and Shigella species and their multidrug resistance patterns among pediatric populations in Ethiopia: a systematic review and meta-analysis - Mihret Tilahun; Melaku Ashagrie Belete; Alemu Gedefie; Habtu Debash; Ermiyas Alemayehu; Daniel Gebretsadik Weldehana; Hussein Ebrahim; Ousman Mohammed; Bruktawit Eshetu; Saba Gebremichael Tekele; Zewudu Mulatie; Agumas Shibabaw (BMC Infectious Diseases)
Abstract Background Salmonella and Shigella are major enteric pathogens that cause diarrhea in children worldwide. They are pathogenic microbes that cause significant diarrheal morbidity and mortality in under five children in resource limited countries. Thus, this systemic review and meta-analysis aimed to investigate the prevalence of Salmonella and Shigella species and their multidrug resistance patterns in pediatric populations in Ethiopia. Methods The articles were searched extensively in the electronic databases and grey literature using entry terms or phrases. Studies meeting the eligibility criteria were extracted in MS Excel and exported for statistical analysis into STATA version 14 software. The overall pooled prevalence of Salmonella and Shigella species was computed using a random-effects model. Heterogeneity was assessed using the Cochrane Q test and I2 statistics with corresponding p-values. Publication bias was assessed using a funnel plot and Egger’s test. In addition, sensitivity analysis was performed to determine the impact of individual studies on the pooled effect size. Result Of a total of 742 identified studies, 89 studies were eligible for full-text analysis. Of 89 studies, 21 were included for meta-analysis involving 5318 study participants. These eligible studies reported a total of 593 bacterial isolates. The overall pooled prevalence of Salmonella and Shigella among pediatrics in Ethiopia was 10.70% (95% CI: 8.96–12.45), with substantial heterogeneity (I2 = 82.1%, p < 0.001) across the studies. The pooled prevalence of Salmonella and Shigella individually among pediatrics in Ethiopia was 15.43% (95% CI: 10.42–20.72) and 15.83% (95% CI: 11.40–20.40), respectively. Moreover, the overall prevalence of multidrug resistance in Salmonella and Shigella isolates was 81.03% (95% CI: 77.39–84.67) with substantial heterogeneity of I2 of 95%, p < 0.0001 between the pooled prevalence of the two species. Conclusion The pooled prevalence of Salmonella and Shigella and their multidrug resistance were alarmingly high in pediatric. The initial empirical treatment of pediatrics patients remains challenging and results high prevalence of antimicrobial resistance. Thus, appropriate infection prevention and control strategies should be implemented and treatment should be directed based on antimicrobial stewardship protocols.